The attitude of online fans: perceived value, expectation, and identification on VAR satisfaction - Deng, Pei; Yan, Weihua; Yu, Ying; Zhang, Yeqin; Zhang, Liqing (Frontiers in Psychology, 2024)
This study explores online fan satisfaction with the Video Assistant Referee (VAR) during the FIFA World Cup Qatar 2022. A structural equation model comprising perceived value, fan expectation, fan identification, and fan satisfaction was run. The online questionnaires were distributed among Chinese football fans. A total of 224 valid responses were received. Using indicators like Cronbach’s alpha coefficient, Kaiser-Meyer-Olkin (KMO) statistic, and Bartlett’s test of sphericity, the results were assessed for reliability, validity, and suitability. From the statistical results, the overall satisfaction of fans with VAR is the middle. Both fan expectation and perceived value positively affect satisfaction (p < 0.01); the path coefficients were 0.26 and 0.57. Contrastingly, fan identification exerts no significant effect on fan satisfaction (p > 0.05); and fan expectation indirectly affects fan satisfaction through perceived value (p < 0.01); the path coefficient was 0.29. The highest effect value for fan satisfaction is perceived value, followed by fan expectation. Consequently, to improve online fan satisfaction with VAR, researchers should focus on perceived value. This research contributes to a greater more comprehensive of Chinese online fans’ preference towards VAR at the FIFA World Cup Qatar 2022.